Disseminated alveolar echinococcosis in a patient diagnosed by metagenomic next-generation sequencing: A case report - Qu, Junyan; Xu, Huan; Lv, Xiaoju (Frontiers in Public Health, 2022)
Background Alveolar echinococcosis (AE) is a parasitic zoonosis with high mortality and disability rates. Diverse clinical manifestations and mimicking of differential diagnoses such as tuberculosis and malignancy pose a diagnostic dilemma. With the rapid development of molecular diagnostic techniques in recent years, metagenomic next-generation sequencing (mNGS) has become an attractive approach for the etiological diagnosis of infectious diseases. Case presentation we report a case of 51-year-old Chinese Tibetan male presented with 3-year low-back pain and 4-month discomfort in the right upper quadrant of the abdomen. He had been in good health. He was diagnosed with tuberculosis and was given anti-tuberculosis treatment a month prior to the visit, but the symptoms were not relieved. Abdominal computerized tomography (CT) revealed a hypodense lesion with uneven enhancement in the liver, and two ring-enhancing cystic lesions in the right abdominal wall. Lumbar spine enhanced MRI showed lesions of mixed density with uneven enhancement in the L1 vertebra and paraspinal tissue. The pathological results of the liver biopsy revealed parasitic infection and possibly echinococcosis. The metagenomic next-generation sequencing (mNGS) of the puncture fluid of abdominal cysts using Illumina X10 sequencer revealed 585 sequence reads matching Echinococcus multilocularis. Disseminated AE was diagnosed. Albendazole (400 mg, twice daily) was used, and the patient was in stable condition during follow-up. Conclusions mNGS may be a useful tool for the diagnosis of AE. The case would help clinicians to improve their diagnostic skills.